Penerapan Metode Layanan Bimbingan Kelompok melalui Problem Solving dalam Meningkatkan Keberanian Berbicara Ketika Diskusi Pada Siswa SMP Negeri 1 Kampar Kiri Hilir - L, Widiyah (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2017)
Courage to talk when the discussion becomes a form of ability in conveying opinions. For students speaking in front of the class not all are able to do it. As a junior high school student N 1 Kampar Kiri Hilir, in expressing his opinion on a discussion almost mostly feel ashamed or not confident. Through classroom action research on counseling guidance applied the method of group guidance services in improving courage to speak in front of the class. The results showed that the acquisition of learning outcomes through problem solving research cycles I, II and III on the role of BK in making students dare to speak in the discussion considered successful because increased student courage continues to increase. Keywords: Methods of Group Guidance Services, Courage Speaks During Discussion